Image Processing Categorization and Fuzzy Logic: A Survey - Nityaselvy, K.; Ramachandiran, R. (IJRDO -Journal of Computer Science Engineering, 2015)
ct Image categorization is one of the critical performances in sensing the crops from slightly sensed data as planning of crops is a composite activity which in turn is an main parameter for design and managing of irrigation facility area. categorized remotely sensed data into a thematic map remains a challenge because many factors, such as the complexity of the landscape in a study area, selected distantly sensed data, and image-processing and organization approaches, may affect the success of a classification.